Proficiency markers of the motivation- and value-related components of the professional competence to be acquired by the specialists in the field of processing and food production - Novikova Viktoriia (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2020)
The purpose of the research is to define the proficiency state of the motivation- and value-related components of the professional competence acquired by the specialists in the field of processing and food productions (based on the results of the experiment which involved the first-year students specialised in 181 "Food technologies"). To determine the proficiency of level of the motivation- and value-related components of the professional competence to be acquired by the future specialists in the field of processing and food productions we used the methodologies adapted to our research: the testing of person’s value-related reference points and the testing of person’s capacity for self-discovery. The experiment was aimed at revealing and comparing future specialists’ motivation to study, basic reasons for educational activity, grounds for choosing a profession, and value-related orientations of the students constituting experimental and control (general) groups. The experiment involved the students specialised in 181 "Food technologies" in Kharkiv State University for Food Technologies and Trade, Kharkiv Petro Vasylenko National Technical University of Agriculture and Kharkiv Cooperative Trade and Economic College. The experiment consisted of two stages. At the first stage, 237 future specialists participated in the continuous questioning specially elaborated by the author. On the second stage, the first-year (two groups) and the second-year students (two groups) were tested according to the methodology "Motivation for study": test 1 "Studying the reasons of students’ educational activity”, test 2 "The necessities to develop students’ self-evaluation". The future specialists in the field of processing and food production acquired the professional competencies during the pedagogical events facilitating the development of stable motivation for their professional activity. The experiment allowed us to affirm that the professional competence demonstrated by the future specialists in the field of processing and food productions consists of some components, the motivation- and value-related component being one of them. On the whole, the results of the questioning confirmed the insufficient (reproductive) proficiency level which the future specialists of processing and food production demonstrated within the professional competence. The results of the first stage of the experiment (continuous questioning) testify that it is important for most students rather to get an appraisal than acquire knowledge. Most students failed to give any reasons for self-perfection or systematic professional development.